Nell-1 Is a Key Functional Modulator in Osteochondrogenesis and Beyond. (December 2019) - Li, C.; Zhang, X.; Zheng, Z.; Nguyen, A.; Ting, K.; Soo, C.
Neural EGFL-like 1 (Nell-1) is a well-studied osteogenic factor that has comparable osteogenic potency with the Food and Drug Administration–approved bone morphogenic protein 2 (BMP-2). In this review, which aims to summarize the advanced Nell-1 research in the past 10 y, we start with the correlation of structural and functional relevance of the Nell-1 protein with the identification of a specific receptor of Nell-1, contactin-associated protein-like 4 (Cntnap4), for osteogenesis. The indispensable role of Nell-1 in normal craniofacial and appendicular skeletal development and growth was also defined by using the newly developed tissue-specific Nell-1 knockout mouse lines in addition to the existing transgenic mouse models. With the achievements on Nell-1's osteogenic therapeutic evaluations from multiple preclinical animal models for local and systemic bone regeneration, the synergistic effect of Nell-1 with BMP-2 on osteogenesis, as well as the advantages of Nell-1 as an osteogenic protein with antiadipogenic, anti-inflammatory, and provascularized characteristics over BMP-2 in bone tissue engineering, is highlighted, which lays the groundwork for the clinical trial approval of Nell-1. At the molecular level, besides the mitogen-activated protein kinase (MAPK) signaling pathway, we emphasize the significant involvement of the Wnt/β-catenin pathway as well as the key regulatory molecules Runt-related transcription factor 2 (Runx2) in Nell-1-induced osteogenesis. In addition, the involvement of Nell-1 in chondrogenesis and its relevant pathologies have been revealed with the participation of the nuclear factor of activated T cells 1 (Nfatc1), Runx3, and Indian hedgehog (Ihh) signaling pathways, although the mechanistic insights of Nell-1's osteochondrogenic property will be continuously evolving. With this perspective, we elucidate some emerging and novel functional properties of Nell-1 in oral-dental and neural tissues that will be the frontiers of future Nell-1 studies beyond the context of bone and cartilage. As such, the therapeutic potential of Nell-1 continues to evolve and grow with continuous pursuit.